Development of Neurobehavioral Deterioration Risk Prediction Model for Welder: A Proposed Study - Paiman, Nuur Azreen; Hariri, Azian; Masood, Ibrahim; Noor, Arma; Yusof, Khairul Hazdi; Abdullah, Samsuri; Idris, Ahmad Fu'ad; Mohd Afandi, Mohd Azizi; Asmuin, Nor Zelawati; Leman, Abdul Mutalib (International Journal of Integrated Engineering, 2018)
Risk prediction model estimate the risk of emerging upcoming outcomes for individual based on severalunderlying characteristics. In welding process, welders have the high risk to expose with the toxicant element whichcan harm the neuropsychological of a welder. This proposed study will develop a prediction model onneurobehavioral deterioration risk of welders. In order to get the intensity of heavy metal exposure of the welders,airborne personal monitoring and toenail biomarker test will be carried out. Meanwhile, for the neurotoxicityassessment, the workers will undergo the neurobehavioral core test battery and questionnaire survey to identify theneurobehavioral score level. Detail statistical analysis between both assessment results will be carried out fordevelopment of prediction model based on artificial neural network. After validation test, the developed artificialneural network prediction model will be applied to another metal base industry for verification purpose. Length ofabstract can be proportional to the length of the article. Through this study, it is expected neurobehavioral riskprediction model on detection on early symptoms of neurobehavioral deterioration will be developed This studycontribute to better understanding on the effects of heavy metals exposure, especially to central nervous systemsamong welders